The Design of Project Risk Management to Mitigate Project Delay in the Onshore Construction Industry (A Case Study of a Shore Protection Project) - Firdaus Yusri Muhammad; Gatot Yudoko; Muhammad Hanafi (Management Analysis Journal, 2025)
This study research focuses on a three-month delay in a shore protection project undertaken by PT Sabar Sejahtera, which resulted in financial, time, and opportunity losses. Electricity is essential for human life and can be generated in various ways; therefore, the construction of power plants must be well planned. Effective project planning helps manage resources and schedules, while poor planning can lead to project delays. This study aims to identify the root causes of the delay, propose solutions and mitigation plans, and develop a lessons learned register. A mixed-method approach was employed, including focus group discussions and Risk Priority Number (RPN) analysis. The Current Reality Tree identified two main root causes: systematic errors during the tendering and planning stages and the absence of a mitigation plan. The Future Reality Tree demonstrated that involving multiple departments and correcting systematic errors could prevent similar issues in future projects. To manage project risks, this study applied the PMBOK 6th Edition project risk management framework, covering risk identification through monitoring. The lessons learned register highlights the importance of early planning, appropriate working methods, and a comprehensive risk mitigation plan. The company is encouraged to adopt this approach in future projects.